A short bout of HFD promotes long-lasting hepatic lipid accumulation. (3rd February 2016) - Chiazza, Fausto; Challa, Tenagne D; Lucchini, Fabrizio C; Konrad, Daniel; Wueest, Stephan
Abstract: A short bout of high fat diet (HFD) impairs glucose tolerance and induces hepatic steatosis in mice. Here, we aimed to elaborate on long-lasting effects of short-term high fat feeding. As expected, one week of HFD significantly impaired glucose tolerance. Intriguingly, recovery feeding with a standard rodent diet for 8 weeks did not fully normalize glucose tolerance. In addition, mice exposed to a short bout of HFD revealed significantly increased liver fat accumulation paralleled by elevated portal free fatty acid levels after 8 weeks of recovery feeding compared to exclusively chow-fed littermates. In conclusion, a short bout of HFD has long-lasting effects on hepatic lipid accumulation and glucose tolerance.